O discurso sobre o jornalismo: uma análise discursiva das lives de Jair Messias Bolsonaro - Fontana, Denise Nunes (2023)
This dissertation examines President Jair Messias Bolsonaro's discourse on journalism during the “Lives de Quinta”, live streams conducted on his official YouTube channel in the years 2020 and 2021. Situated within the realm of Social Communication, this study aligns with Pêcheux's Discourse Analysis (DA) framework to scrutinize the meaning’s effects of these discourses. The central inquiry addressed is as follows: What social and discursive positions underlie President Jair Messias Bolsonaro's discourse on journalism? To address this, we endeavor to fathom the discursive mechanism through which the president articulates his views on journalism, identifying the underlying Discursive Formation and its meaning’s effects. Additionally, we delve into how Jair Messias Bolsonaro's social position influences his discursive orientation. Furthermore, this endeavor seeks to deliberate on the interplay of official discourse within the dichotomy of credibility and skepticism inherent in journalistic practice. We draw upon Pêcheux (1997, 1995, and 1983) to comprehend foundational notions for conducting analysis. Furthermore, we refer to Charaudeau (2011 and 2018), Grigoletto (2005), and Orlandi (2012 and 2020) to address concepts such as communication contract, discursive location, and discursive formation. Meanwhile, Benetti (2007 and 2016), Pires and Carvalho (2022), Serrano (2006), Traquina (2005), and Lisboa (2012) assist us in gaining a deeper understanding of journalism and related theoretical concepts. The methodology encompasses visual analysis of live broadcasts, transcriptions of segments where Bolsonaro expounds on the press. A total of 15 live streams underwent meticulous scrutiny, with this investigation spotlighting 50 exemplary Discursive Sequences (DS) to elucidate the discursive process. The primary findings unearth that Bolsonaro's discourse on journalism is concretized by two distinct social positions: the Presidential Social Position and the Captain Social Position. These dual societal anchors govern the discursive stances adopted within the two identified Discursive Formations. When aligned with FD1: Objective journalism, the president assumes the mantle of the Good Political Discursive Position; conversely, within FD2: The journalism is the enemy, he embraces the Legend's Discursive Position. These outcomes effectively address the research query, underscoring the pivotal role of Bolsonaro's social orientations in shaping his discursive stances. The president's discourse about journalism is thereby molded by the interplay between the Discursive Formation he aligns with and the discursive stance he adopts. This study significantly enriches our comprehension of political discourse and its intricate intertwinement with journalism, while also offering insights into the ongoing dialogue regarding the crisis of the journalistic field's perception.